2002
DOI: 10.1016/s0925-4773(02)00250-2
|View full text |Cite
|
Sign up to set email alerts
|

NZF-2b is a novel predominant form of mouse NZF-2/MyT1, expressed in differentiated neurons especially at higher levels in newly generated ones

Abstract: NZF-2 (MyT1) is a member of C2HC-type zinc finger transcription factors. A novel form of mouse NZF-2 has been isolated. This novel form, NZF-2b, has an additional C2HC-type zinc finger motif. The expression levels of NZF-2b are by far the more predominant than those of the already known form of NZF-2. In embryonic mouse nervous system, the expression of NZF-2b starts as early as at 9.5 days post-coitum (dpc) in newly differentiated neurons in the central nervous system (CNS) and the peripheral nervous system (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 11 publications
0
37
0
Order By: Relevance
“…These two isoforms differ in their Nterminal 100 amino acid residues (Matsushita et al, 2002), such that NZF2b has an extra zinc finger (MYT1a has 6 zinc fingers and NZF2b has 7 zinc fingers). For simplicity, we refer to both RNA isoforms from the Myt1 locus as Myt1, and we refer to the 6-zinc-finger Myt1 cDNA as Myt1a (Kim et al, 1997a;Matsushita et al, 2002). Our semi-quatitative RT-PCR results showed that Myt1a and Nzf2b are both expressed in the developing pancreas, with Nzf2b being expressed at much higher levels (data not shown).…”
Section: Myt1mentioning
confidence: 99%
“…These two isoforms differ in their Nterminal 100 amino acid residues (Matsushita et al, 2002), such that NZF2b has an extra zinc finger (MYT1a has 6 zinc fingers and NZF2b has 7 zinc fingers). For simplicity, we refer to both RNA isoforms from the Myt1 locus as Myt1, and we refer to the 6-zinc-finger Myt1 cDNA as Myt1a (Kim et al, 1997a;Matsushita et al, 2002). Our semi-quatitative RT-PCR results showed that Myt1a and Nzf2b are both expressed in the developing pancreas, with Nzf2b being expressed at much higher levels (data not shown).…”
Section: Myt1mentioning
confidence: 99%
“…As for the last alternative, in situ expression data indicate that the MyT1 isoforms are expressed in newly generated neurons throughout the CNS, including RGCs. Thus, the regulation of MyT1 expression could then allow newly generated cells to escape from Notch inhibition [Matsushita et al, 2002]. Further experimentation will be necessary to determine the respective contributions of these mechanisms in mediating the inhibition of Notch activity in differentiating ganglion cells.…”
Section: Downregulation Of Notch Activity Drives Early Progenitor Celmentioning
confidence: 99%
“…Both Myt1 and Myt1L proteins reside in distinct domains within the neuronal and oligodendrocyte nuclei, expressed as discrete patterns (Armstrong et al 1995;Kim et al, 1997) and they interact with the corepressor Sin3B and actively recruit HDAC1 and HDAC2 to specific genes (Romm et al, 2005). The NZF-2/Myt1 comprises two isoforms, the poorly expressed NZF-2a/Myt1 (6-zinc finger form) and the predominant NZF-2b/7ZFMyt1 (7-zinc-finger form), located on chromosome 20 and 2 of human and mouse, respectively (Nagase et al, 1998;Kikuno et al, 1999;Matsushita et al, 2002;Deloukas et al, 2002;Nielsen et al, 2004). But the role of these two isoforms in neurons is poorly known.…”
Section: Introductionmentioning
confidence: 99%